You Are What Your Mother Endured: Intergenerational Epigenetics, Early Caregiving, and the Temporal Embedding of Adversity. (23rd January 2022) - Lappé, Martine; Jeffries Hein, Robbin
Abstract: Environmental epigenetics has become a site of growing attention related to the intergenerational effects of stress, trauma, and adversity. This article draws on a multi‐sited ethnography of epigenetic knowledge production in the United States and Canada to document how scientists conceptualize, model, and measure these experiences and their effects on children's neurodevelopmental and behavioral health. We find that scientists' efforts to identify the molecular effects of stress, trauma, and adversity results in a temporal focus on the mother–child dyad during early life. This has the effect of biologizing early childhood adversity, positioning it as a consequence of caregiving, and producing epigenetic findings that often align with individually oriented interventions rather than social and structural change. Our analysis suggests that epigenetic models of stress, trauma, and adversity therefore situate histories of oppression, inequality, and subjugation in discrete and gendered family relations, resulting in the temporal embedding of adversity during early life.